Longitudinal Conjoint Patterns of Alcohol and Tobacco Use Throughout Emerging Adulthood. (23rd February 2017) - Cance, Jessica Duncan; Talley, Anna E.; Morgan-Lopez, Antonio; Fromme, Kim
ABSTRACT: Background: The concurrent use of alcohol and tobacco has a multiplicative effect on both social and physical consequences. While it is known that alcohol and tobacco use are strongly correlated in emerging adulthood, there is significant individual variability in use. However, little research has examined how patterns of concurrent use are related over time. Objectives: The current study explores these longitudinal conjoint trajectories, as well as the associated sociodemographic factors. Methods: We used sequential latent class growth analysis to explore the co-occurring longitudinal patterns of recent alcohol and tobacco use across emerging adulthood (10 data collection periods, 2004-2009) with a diverse sample of 2, 244 college students (60% female; 54% White). Results: Twenty distinct patterns of conjoint alcohol and tobacco use were found. There was more variation in tobacco use trajectories among alcohol users than variation in alcohol trajectories among tobacco users. Using multinomial logistic regression models we determined the impact of sociodemographic characteristics on classification into each conjoint pattern versus the normative trajectory (Abstaining tobacco/Low alcohol). Male gender, White race, fraternity/sorority affiliation, and higher family income were significantly associated with riskier conjoint trajectory patterns. Conclusions/Importance: Findings highlight the diversity of alcohol and tobacco use behaviors across emerging adulthood. The low variation in alcohol use among tobacco users indicates that tobacco use is a significant risk factor for heavier drinking. A better understanding of the covarying use of these two ubiquitous substances may provide new avenues for preventing and reducing the use of both.